Seismicity and focal mechanism of earthquakes in Andaman Islands (MAUSAM, 1979)
Spatial distribution and temporal variation of earthquakes in Andaman-Nicobar Islands have been studied with the help of data from 1917 through 1974. Cross-sections showing the epicentral distribution versus focal depth along four zones in the region, were drawn to understand the nature of the dipping of the Indian plate. Earthquake recurrence curves were drawn for an area of 100 km radius around Port Blair Observatory for events upto the lowest magnitude 2 based on data during 1967-1974 and compared with these for the complete region for all the events recorded during 1964-1974 and also since 1917. Focal mechanisms of earthquakes are also discussed in the light of regional plate tectonics. Normal as well as thrust faulting was observed for earthquakes in the region. The agreement between the focal mechanism solutions and the regional tectonics was relatively better in the Nicobar Islands region as compared to that in the Andaman Islands. Seismicity increase followed by decrease was also noticed prior to some earthquakes close to Andaman Islands.